Facebook Exposure on Students’ Essay Writing Proficiency - Geryl Cataraja; Jahara Mae E. Monares; Honeyly D. Losa; Joshua R. Villardo (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study was to determine the effect of Facebook Exposure on Students’ Essay Writing Proficiency to the Science Technology Engineering and Mathematics (STEM) students of Palompon Institute of Technology (PIT). The researchers conducted a survey on the randomly selected 150 STEM students. The findings showed that students needs improvements on their essay writing skills. In addition, students should limit the number of hours they spent on Facebook and focus more on learning or use Facebook as a way or tool for education and not just for entertainment.